Salas de recursos multifuncionais: uma revisão integrativa a partir de teses e dissertações - Follmann, Ligiane (2022)
Public educational policies aiming special education propose the installation of Multifunctional Resource Rooms (MRR) in schools to serve students and complement the schooling of students with intellectual disabilities, neuromotor physical disabilities, global developmental disorders, specific functional disorders and high abilities or giftedness, enrolled in the Education Network institutions. Considering the magnitude of aspects related to the insertion of Multifunctional Resource Rooms in the school environment, which include the relevant legislation, installation requirements and the attributions given to the teacher who works in these spaces, it is natural to expect that academic research will be developed that address themes related to these spaces. In this sense, the main goal of this work is to carry out an integrative review of scientific production in theses and dissertations produced in Brazil that deal with the subject “Resource Room” in order to characterize academic research in relation to the predominant themes and objectives. It is intended to build a descriptive scenario of the predominant themes in academic research that deal with MRR and to investigate how academic research reflects about the functions and functioning of these spaces, seeking to establish a relationship between research and the actions performed. To carry out the research, we chose to use the Brazilian Digital Library of Theses and Dissertations as a source of documents to be reviewed and defined the period between 2016 and 2020 as a time frame. Data collection resulted in 175 documents, 32 of which were theses and 143 dissertations, which were submitted to a qualitative analysis inspired by content analysis techniques, which allowed the grouping of works in classes created considering similarity criteria. According to the classification criteria used, a total of 05 classes emerged: AEE Student (Specialized Educational Service), Educational Policies, Teacher Training, Interaction, and Pedagogical Resources. The predominance of works whose theme is the included student was observed, with 42% of the total production, followed by themes on educational policies in the scope of inclusion, with 32% of the works in the sample. The works associated with other classes, which reaches 26% of the total production, call attention to the need for study and specific knowledge on the subject, highlighting the importance of the role of teachers, both in the regular classroom, as well as the AEE and the team. teachers involved in the process of teaching inclusion students, developing and promoting pedagogical practices appropriate to the public served. The integrative review presented here contributes to the construction of a scenario on the predominant research interests throughout the analysed clipping, and, by revealing the breadth of the researched themes and presenting a broad and updated scenario on academic research, this work contributes to the filling gaps in knowledge the Multifunctional Resource Rooms.